Kemandirian Anggota Kelompok Tani dalam Berusahatani Padi di Kecamatan Polanharjo Kabupaten Klaten - Ghifari, Muhammad Fuad; Sugihardjo, Sugihardjo; Suwarto, Suwarto (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2024)
Klaten Regency is dominated by the agricultural sector, especially rice. Rice productivity in Klaten Regency has decreased from year to year. This is due to the lack of ability of farmers to create independence in rice farming. The independence of farmer group members will run smoothly if the farmers in Polanharjo District are able to consciously take the initiative in creating independent farming for more advanced agriculture. This study aims to 1) analyze the independence of farmer group members in cultivating rice 2) analyze the factors forming the independence of farmer group members in cultivating rice 3) analyze the relationship between the factors forming the independence of farmer group members and the independence of farmer group members in cultivating rice in Polanharjo District, Klaten Regency. The method used in this research is quantitative with the Spearman Rank test..